Predicting microRNAs and their Target Genes Involved in Sepsis Pathogenesis by using Bioinformatics Methods - Musavi, Maryam; Haftcheshmeh, Saeed Mohammadian; Fazel, Hadi; Momtazi-Borojeni, Amir Abbas (Current Pharmaceutical Design, 2025)
IntroductionSepsis, like neutropenic sepsis, is a medical condition in which our body overreacts to infectious agents. It is associated with damage to normal tissues and organs by the immune system, which leads to the spread of inflammation throughout our body. Of note, microRNAs (miRNAs) have been found to have a critical role in the sepsis progression. Such miRNAs are registered in the miRNA databases, such as Gene Expression Omnibus (GEO), with a specific identifier and unique characteristics. There is also computational software, such as TargetScan, that are broadly employed for the analysis of miRNAs, including their identification, target prediction, and functional analysis.MethodsThe current in-silico study aimed to predict miRNAs involved in sepsis progression. To this end, the GEO database was employed to find the sepsis-related genome profile. Afterward, down-regulated genes were selected for further bioinformatics analysis with the assumption that their decreased expression is associated with an increased sepsis progression. The miRNAs complementary to the selected genes were then predicted using TargetScan software. Based on the current in-silico analysis, seven miRNAs, including hsa-miR-325-3p, hsa-miR-146a-3p, hsa-miR-126-5p, hsa-miR-22-3p, hsa-miR-223-3p, hsa-miR-145-5p, and has-miR-181 family, were predicted to participate in sepsis pathogenesis. Among the predicted miRNAs, hsa-miR-325-3p has not been previously predicted or validated to be involved in septic conditions.ResultsOur prediction results showed that hsa-miR-325-3p may target genes implicating in both anti-(ETFB gene) and pro-inflammatory (TCEA1 and PTPN1 genes) responses, suggesting it is an immune hemostasis regulator during sepsis inflammation. Although the role of other predicted miRNAs has been already validated in the sepsis pathogenesis, the current study predicted new targets of these miRNAs, which have not been reported by previous in-silico or experimental studies on sepsis and other pathogenic conditions. Notably, other miRNAs, including hsa-miR-146a-3p, hsa-miR-126-5p, hsa-miR-22-3p, hsa-miR-223-3p, and hsa-miR-145-5p were predicted to target genes participating in inflammatory responses, including BLOC1S1, POLR2G, PTPN1, TCEA1, and CCT3.ConclusionIn conclusion, the results of the present study can provide promising targets as therapeutic and diagnostic tools to treat and manage inflammation sepsis, such as neutropenic sepsis. However, these findings should be further evaluated in experimental studies to find their exact effects and underlying mechanisms.
Keywords: microRNAs